Peranan Pembimbing Kemasyarakatan Terhadap Anak Yang Berhadapan Dengan Hukum Pada Balai Pemasyarakatan Klas I Makassar (PETITUM, 2014)
The Role of Social Guide of Child Who Violate the Law of Balai Pemasyarakatan Kelas I Makassar (guided by Muliati Pawennei and Syamsiar Arief) The goal of this research is for knowing and analizing how efficient the role of Social guide of child who violate the law, and for knowing what the abstracle factor in implementation of role of society guide of child who violate the law of Balai Pemasyarakatan Kelas I Makassar. This research running by normative empirical research type in focus role social quide of child who violate the law focus in field and library research, by using descriptive method. 7he result of this research show that the role of social guide is very needed of role of social quide of child who violate the law. The official of social quide has role in doing social research start from investigating in polce force, demanding in judiciary and juridiction violate the law case.